Efficacy and safety of ixekizumab treatment in patients with axial spondyloarthritis: 2-year results from COAST. Issue 2 (19th July 2022) - Braun, Jürgen; Kiltz, Uta; Deodhar, Atul; Tomita, Tetsuya; Dougados, Maxime; Bolce, Rebecca; Sandoval, David; Lin, Chen-Yen; Walsh, Jessica
Abstract : Objectives: To study the efficacy and safety of ixekizumab (IXE) in patients with radiographic (r-) and non-radiographic (nr-)axial spondyloarthritis (axSpA) for up to 116 weeks. Methods: COAST-Y (NCT03129100 ) is the 2-year extension study following COAST-V, COAST-W and COAST-X. Patients were treated with either 80 mg IXE every 4 weeks or 2 weeks, as assigned in the originating studies. Efficacy was assessed in all participants continuously treated with IXE through week 116 and in subgroups based on disease subtype and dosing. Missing data were handled by non-responder imputation for categorical variables and modified baseline observation carried forward for continuous variables. Safety data were analysed in all patients having received ≥1 IXE dose. Results: Of 932 patients who received ≥1 IXE dose, 773 enrolled in COAST-Y (82.9%); 665 of which (86.0%) completed week 116. Of 352 continuously treated patients, the proportion achieving Assessment of Spondyloarthritis International Society (ASAS40) at week 52 was 51.4%, which increased to 56.0% at week 116. The proportion of patients achieving ASAS40 at week 116 was 64.9% and 57.7% for biological disease-modifying antirheumatic drug (bDMARD)-naïve patients with r-axSpA and nr-axSpA, respectively, and 47.0% for TNFi-experienced patients. The proportion of patients achieving Ankylosing Spondylitis Disease Activity Score <2.1 through week 116 was 57.0% and 52.9% for bDMARD-naïve patients with r-axSpA and nr-axSpA, respectively, and 33.6% for TNFi-experienced patients. Incidences of treatment-emergent adverse events and serious adverse events were consistent with previous reports. Conclusion: IXE treatment led to sustained long-term improvements in patients with axSpA, with similar efficacy for r-axSpA and nr-axSpA, and for patients receiving the approved every 4 weeks dose. The safety profile of IXE was consistent with previous reports. No new safety signals were identified.